Validation of coupled GCM and projection of summer rainfall change over South Africa by the use of Statistical downscaling method - (:unkn) unknown (My University, 2005)
In this study, the southern African climate response to increasing amounts of greenhouse gases is investigated, based on the dataset of a 150-yr climate change experiment following the IPCC Special Report on Emissions Scenarios marker scenario B2 (SRES-B2) performed with the coupled ARPEGE/OPA/GELATO general circulation model (GCM). The method of canonical correlation analysis (CCA) is adopted to validate the ability of the GCM to simulate the present-day climate over the southern African region and project the late-summer rainfall change over South Africa at the end of the 21st century. The model validation shows that the ARPEGE/OPA/GELATO GCM is able to capture the observed link between rainfall over South Africa and adjacent sea-level pressure (SLP), despite the existence of some systematic errors. The structure and variability of SLP are reproduced by the GCM in a realistic way. The major controlling mechanism of rainfall over South Africa can be identified in the GCM. The projection of rainfall indicates a drying trend during the 21st century over most parts of South Africa, in particular the central interior. Compared to present-day climatology, the overall late-summer rainfall will decrease by 8.2% by the end of 21st century as derived from GCM grid-point output, and by 16.1% from the downscaling model.
Keywords: African Research